Analog Shocking Therapy Sebagai Metode Katarsis Terhadap Ketenangan Jiwa pada Karyawan - Mohammad Aqil Baihaqi; Dian Siti Nurjanah; Medina Chodijah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
This research is backed by the many problems experienced by employees who suffer from mental unrest that can inhibit the productivity of work in the scope of work especially in the company. The purpose of this research is to know the condition of the souls of employees, as well as the process in conducting Analog Shocking Therapy as a cathartic method, and to know the Analog Shocking Therapy as a cathartic method of the employee's mental tranquility. The method of study used is a method of mixture with an expressive sequential strategy, by taking and processing quantitative data first then deesed through a qualitative interview. The results obtained from this study showed that the low mental peace conditions experienced by employees before therapy using Analog Shocking Therapy as much as 51%, the data showed that many employees experienced Low mental peace conditions. The stage in implementing Analog Shocking Therapy is that the client is invited to do a visualization by creating the parable of the ball as a medium to transfer the negative emotions that have been experienced. And Analog Shocking Therapy as a cathartic method of the peace of mind of the employees showed that experienced employees after the therapy experienced a change of self becomes more spirited, more optimistic, easier in controlling fear, worry, and anger at work.